METODE PENDIDIKAN INABAH DALAM MENGATASI KENAKALAN REMAJA PONDOK PESANTREN SURYALAYA - Sahliah, Sahliah; Hanipah, Siti (Prodi PAI IAILM Suryalaya, 2019)
This study aims to determine how the educational method ofdealing with juvenile delinquency in handling juvenile delinquencyusing the Inabah rehabilitation method at Suryalaya Islamic BoardingSchool. The results of the study revealed that juvenile delinquencycarried out by children built before Inabah is drunk, often skips schooland is involved in the use of illegal drugs after completing education.Juvenile delinquency is divided into two, namely two-dimensionalvictims and five-dimensional victims with different levels of effect oneach offender. Awareness or education methods consist of: bathingrepentance, prayer fardlu and sunnah, dzikir jahar and dhikr khofi,talqin dzikir, fasting, other beneficial activities, and health checks andeducation skills. The way to overcome juvenile delinquency is throughinabah education method in Suryalaya Islamic Boarding Schoolconsists of three stages, namely the rejection stage, the acceptancestage and the habituation stage. While the success of the Inabah methodin overcoming juvenile delinquency is shown by the existence of medicalawareness and spiritual awareness.